Non-native species introductions, invasions, and biotic homogenization in the Atlantic Forest - Vitule, Jean R. S.; Occhi, Thiago V. T.; Carneiro, Laís; Daga, Vanessa S.; Frehse, Fabrício A.; Bezerra, Luis A. V.; Forneck, Sandra; de Pereira, Hugo S.; Freitas, Matheus O.; Hegel, Carla G. Z.; Abilhoa, Vinícius; Grombone-Guaratini, Maria T.; et al. (Springer Nature, 2021)
Anthropogenic introduction of non-native species has occurred since the first European colonization of South America in the 1500s, with the Atlantic Forest being the most heavily affected biome in the continent. Biological invasions, together with other anthropogenic pressures occurring over the subsequent 500 years, led to many biological changes such as biotic homogenization. In this chapter, we discuss patterns of non-native species introductions, highlight invasions or population explosions of problematic native species, and explore the phenomenon of biotic homogenization in the Atlantic Forest, Brazil. We explore examples related to the effect of recent introductions of non-native species, highlighting the loss of native biodiversity (e.g., rare, specialist, and endemic) and the proliferation of human-mediated non-native species of economic importance (e.g., genrealist, common and widely distributed). We also discuss the role of society and policymakers in developing policies of public interest. Finally, we discuss how raising awareness of the negative effects of invasive non-native species will contribute to inform management policies and provoke more in-depth research, resulting in greater protection and sound management strategy for the Atlantic Forest.
Keywords: Alien species; Biotic changes; Hot spot of biodiversity; Human-mediated species introductions